Strategi Pembelajaran Fiqih dengan Pendekatan Kontekstual Mengaitkan Hukum Islam dengan Kehidupan Sehari-hari di SMAN 1 Cihaurbeuti Kabupaten Ciamis - Yanto Maulana Restu; Mohammad Tesar Dzulkipli; Hafidzul Fajar Alamsyah; Yunita Khoirunnisa; Siti Sariatus Sa'adah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to describe how fiqh learning strategies based on a contextual approach (Contextual Teaching and Learning / CTL) are implemented at SMAN 1 Cihaurbeuti, Ciamis Regency, particularly in an effort to connect Islamic law provisions with the realities of students' lives. This study uses a descriptive qualitative research design with data collection techniques that include direct observation of the learning process, in-depth interviews with teachers and students, and a review of relevant learning documents. The findings show that fiqh teachers implement contextual learning through a structured series of processes. The initial stage is realized in lesson planning that deliberately links fiqh material with students' concrete experiences. The next stage is evident in the implementation of learning that utilizes various strategies, such as interactive discussions, simulations, case study analysis, and direct practice related to worship and muamalah activities in daily life. In the evaluation stage, teachers applied authentic assessment by focusing on observing worship practices, project-based assignments, and joint reflection activities. This study also identified factors that influence the successful implementation of CTL, including a religious school atmosphere and adequate teacher competence as supporting factors, while limitations in learning media and time allocation were the main obstacles. In general, the results of the study show that a contextual approach to fiqh learning not only improves students' conceptual understanding but also strengthens their ability to apply Islamic law in real life. Keywords: learning strategies, Islamic Religious Education, fiqh, contextual learning (CTL), Islamic law, SMAN 1 Cihaurbeuti, Ciamis Regency